Perancangan Rangkaian Rectifier Pada Sistem RF Energy Harvesting dengan Antena Televisi pada Frekuensi UHF - Muhammad Novian Rahmatur Rajab (Politeknik Negeri Malang, 2019)
Nowadays, the development of technology is increasing rapidly, one of which is the development of telecommunication technology. Telecomunication provides communication services by using radio waves as information carriers, as a result of the large number of electromagnetic waves in the natural surroundings. From this, various studies have now been developed in order to be able to utilize the energy contained in electromagnetic waves that are around as an alternative energy source, also called Energy Harvesting. The purpose of making this thesisis to make a rectifier and integrated with a television antenna to convert the RF signal at the UHF frequency (470MHz-807 MHz) into DC voltage energy as an Energy Harvesting system. In this final project, a 2.4 and 6-stage voltage douber rectifier was designed using the HSMS 2820 diode and integrated with television antenna. The results of the rectifier circuit made are circuit simulation. The rectifier is able to convert the AC input to DC and amplify the output voltage to achieve multiple stages of the circuit used. In the 6-stage rectifier circuit fabrication test, the largest output produced reached 1.3 V with an input of 0.398 V at a frequency of 470 MHz while the output was the smallest is 3 mV with an input of 0.022 V at a frequency of 637 MHz, and in testing using a TV antenna as an RF signal catcher from the transmitter, the largest voltage obtained reaches 1,019 V in a 6-stage circuit, the output voltage is DC voltage.